2019
DOI: 10.1007/s12298-019-00655-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrated approaches to study the drought tolerance mechanism in hot pepper (Capsicum annuum L.)

Abstract: Drought is one of the predominant abiotic stresses which have phenomenal impact on crop productivity. Alterations in aquaporin gene expressions are part of complex molecular responses by plant in response to drought. To better understand the role of aquaporins in economically important crop chilli (Capsicum annuum), drought induced gene expression of twelve aquaporins was determined in drought tolerant-KCa-4884 and drought susceptible-G-4 genotypes. Conjointly, the effect of drought on leaf water status and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 58 publications
1
6
0
8
Order By: Relevance
“…Одночасно оцінювали вплив посухи на стан води в листках та параметри фотосинтезу. Коли рослини чилі зазнали стресу, спричиненого посухою, у посухостійкого генотипу KCa-4884 спостерігалося підвищення експресії PIP1; 1 та PIP1; 2 (Sahitya et al, 2019). Тривалий та посилений посуховий стрес призвів до підвищення рівня експресії досліджуваних генів PIPs (Galmes et al, 2007).…”
Section: участь аквапоринів у захисті від посухиunclassified
See 2 more Smart Citations
“…Одночасно оцінювали вплив посухи на стан води в листках та параметри фотосинтезу. Коли рослини чилі зазнали стресу, спричиненого посухою, у посухостійкого генотипу KCa-4884 спостерігалося підвищення експресії PIP1; 1 та PIP1; 2 (Sahitya et al, 2019). Тривалий та посилений посуховий стрес призвів до підвищення рівня експресії досліджуваних генів PIPs (Galmes et al, 2007).…”
Section: участь аквапоринів у захисті від посухиunclassified
“…Крім того, на думку Ma & Yamaji (2008), NIPs (OsNIP 2; 1 та OsNIP 2; 2) у рослин рису здатні транспортувати більшу кількість розчиненої кремнієвої кислоти, яка посилює стійкість рослин до абіотичних стресів. Таким чином, підвищення експресії NIPs, можливо, забезпечило стійкість до посухи в посухостійкого генотипу KCa-4884 (Sahitya et al, 2019).…”
Section: участь аквапоринів у захисті від посухиunclassified
See 1 more Smart Citation
“…It would also allow in extracting the evolutionarily closest templates for the protein sequences and would aid to improve the accuracy of the conventional template-based protein modeling protocols [82][83][84][85][86][87][88][89][90]. The strategy would be significantly useful for improving the algorithmic accuracy of several related research works including protein modeling [91] and folding [92] and functional enzymatic characterization [93][94][95][96][97][98][99][100].…”
Section: Crucial Residues For Functional Mutagenesis and Directed Evomentioning
confidence: 99%
“…The accordance with the result of Malika et al, [20] who reported a maximum stomatal conductance under water stress and negative effect to photosynthesis and yield in chilli. Drought stress experienced partial stomatal closure by restricting CO 2 influx and production limited photo-assimilates [21]. stress had direct effect on chlorophyll membrane, enzyme denaturation and reduced carboxylation efficiency [22].…”
mentioning
confidence: 99%